Metabolic dysfunction-associated steatotic liver disease as a cardiovascular risk factor - Platek, Anna E.; Szymanska, Anna (Clinical and Experimental Hepatology, 2023)
In recent years, the diagnosis and understanding of nonalcoholic fatty liver disease (NAFLD), recently redefined as metabolic dysfunction-associated steatotic liver disease (MASLD), and its relationship with cardiovascular diseases (CVD) are gaining better understanding. As MASLD shares common risk factors with CVD, including obesity, insulin resistance, hypertension, and dyslipidemia, research increasingly identifies it as a potential independent risk factor for CVD. The exact mechanisms linking MASLD to CVD remain complex and multifaceted, involving metabolic, inflammatory, and vascular pathways. Current cardiology guidelines recognize the significant association between MASLD and CVD, advocating its integration into cardiovascular risk assessment and management. Despite the progress, gaps persist in understanding underlying molecular and cellular mechanisms and the representation of diverse populations in epidemiological studies. The review illuminates the clinical implications of the MASLD-CVD link and identifies directions for future research.